ANALISIS PERSEDIAAN TEPUNG FORMULA SEBAGAI BAHAN BAKU UTAMA PEMBUATAN BROWNIES DENGAN MENGGUNAKAN METODE ECONOMIC ORDER QUANTITY (EOQ) PADA USAHA JEPARA BROWNIES PEKANBARU - Manungkali Muliadi; Daulay Nauli Iwan; Siregar Andreas Prima (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to determine the effect of (1) how much is the optimal amount of raw material purchases, (2) how many the frequency of raw material purchases is, (3) what the total inventory costs are of an efficient resource supply, and (4) when is the right time to reorder point. Economic Order Quantity (EOQ) is a technique for obtaining raw material inventory in a company that determines how many beneficial orders are for each time an order is ordered with a predetermined frequency and when to reorder point. This method aims to minimize total inventory costs. Using this method can also reduce inventory costs so that inventory efficiency is good and the optimal number of order units can be achieved by keeping costs to a minimum. The results showed that (1) the amount of raw material procurement carried out by the Usaha Jepara Brownies Pekanbaru was not optimal, (2) the optimal frequency of raw material procurement was four times a year or once every three months, (3) the Usaha Jepara Brownies Pekanbaru was too wasteful in spending the total inventory cost, and (4) the reorder point implemented by the company has not been regular.Keywords: EOQ, purchase frequency, Total inventory cost, and reorder point